Information Technology Research Challenges for Healthcare: From Discovery to Delivery - Graham, Susan; Estrin, Deborah; Horvitz, Eric; Kohane, Isaac; Mynatt, Elizabeth; Sim, Ida (Computing Community Consortium, 2010)
This paper is an outgrowth of the workshop, "Discovery and Innovation in Health IT," sponsored by the National Science Foundation, the Office of the National Coordinator for Health Information Technology, the National Institute of Standards and Technology, the National Library of Medicine, the Agency for Healthcare Research and Quality, the Computing Community Consortium, and the American Medical Informatics Association. The workshop was held at the Parc 55 Hotel in San Francisco on October 29 and 30, 2009.